How clinically effective is intravascular ultrasound in interventional cardiology? Present and future perspectives. (November 2013) - Nakatani, Shimpei; Proniewska, Klaudia; Pociask, Elżbieta; Paoletti, Giulia; de Winter, Sebastiaan; Muramatsu, Takashi; Bruining, Nico
Intravascular ultrasound (IVUS) has been clinically available for almost 25 years now and showed us valuable information regarding the coronary vessel lumen, its dimensions, the plaque burden and plaque characteristics that we were not able to assess by angiography alone. Using these abilities, IVUS has helped us to start, understand the atherosclerotic process in the coronary vessels. Further technical innovations partially overcame the somewhat limited image resolution of IVUS allowing more in-depth characterization and quantification of coronary plaque components. In addition, IVUS has been shown to be helpful to guide interventional procedures including optimal stent deployment in many clinical situations. In this review, we focus on the potential role of IVUS technology in interventional cardiology and on the valuable role of IVUS usage in percutaneous coronary interventions.